Review: Application of Electronic Computer and Automatic Control System in Forest Fire - Yu Chen (Forest Chemicals Review, 2022)
Forest fire is one of the forest resources disasters in China, and it is also one of the natural disasters that cause serious losses to forest resources in China. Forest fire prevention has always been the focus of forest protection in China. How to prevent forest fire has become an important task of forest resource management. The use of electronic computer and automatic control system in the current forest fire prevention increasingly highlights its importance. This paper analyzes the application of remote sensing technology in forest fire prevention and forest resource management.